2016
DOI: 10.1152/jn.00763.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar contributions to self-motion perception: evidence from patients with congenital cerebellar agenesis

Abstract: Dahlem K, Valko Y, Schmahmann JD, Lewis RF. Cerebellar contributions to self-motion perception: evidence from patients with congenital cerebellar agenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
3
7
0
1
Order By: Relevance
“…However, neural detection thresholds for single otolith afferents are substantially higher (~10 cm/s 2 ) (Jamali et al, 2013; Yu et al, 2015), indicating that pooling the activities of multiple otolith afferents is required to give rise to perception of translational self-motion. By contrast, when considering differences in static head orientation relative to gravity, our results here have shown that single regular otolith afferents display discriminability values that are similar to those reported in psychophysical studies (~2 o ) (Clemens et al, 2011; Valko et al, 2012; Karmali et al, 2014; Janssen et al, 2011; Dahlem et al, 2016; Tarnutzer et al, 2013). This suggests that little additional pooling of afferent activities is actually required.…”
Section: Discussionsupporting
confidence: 85%
“…However, neural detection thresholds for single otolith afferents are substantially higher (~10 cm/s 2 ) (Jamali et al, 2013; Yu et al, 2015), indicating that pooling the activities of multiple otolith afferents is required to give rise to perception of translational self-motion. By contrast, when considering differences in static head orientation relative to gravity, our results here have shown that single regular otolith afferents display discriminability values that are similar to those reported in psychophysical studies (~2 o ) (Clemens et al, 2011; Valko et al, 2012; Karmali et al, 2014; Janssen et al, 2011; Dahlem et al, 2016; Tarnutzer et al, 2013). This suggests that little additional pooling of afferent activities is actually required.…”
Section: Discussionsupporting
confidence: 85%
“…The hypothesis that cerebellar deficits lead to increased vestibular noise fits with results of several other studies that have documented impaired vestibular perception in cerebellar patients [8][9][10]. There is, however, also evidence of impaired visual motion processing in cerebellar patients [11] and perceptual deficits more broadly, particularly in the temporal domain [12].…”
supporting
confidence: 86%
“…Cerebellar agenesis is a rare condition which is mainly associated with motor impairment, postural and balance disturbances (Glickstein, 1994; Velioglu et al, 1998). The absence of cerebellum or its functional disruption can lead to deficits that are not only related to motor processing but also to cognitive functions (Fiez et al, 1992; Arrigoni et al, 2015; Dahlem et al, 2016). Similarly, lesions to basal ganglia are associated with motor deficits and with various cognitive processes (linguistic, attentional, mnestic, and executive); in particular, their dysfunction has been related to neurodevelopmental disorders (Riva et al, 2018).…”
Section: Brain Mechanisms At the Root Of Consciousness And Attentionmentioning
confidence: 99%